Family Relationships and Sexual Orientation Disclosure to Family by Gay and Bisexual Men in Jamaica. Issue 4 (1st October 2016) - White, Yohann; Sandfort, Theo; Morgan, Kai; Carpenter, Karen; Pierre, Russell
ABSTRACT: Gay and bisexual men in Jamaica encounter stigma and discrimination due to criminalization of and negative attitudes towards same-sex sexuality. Disclosure of sexual orientation may be self-affirming, but could increase exposure to negative responses and stressors. Outcomes of an online survey among 110 gay and bisexual Jamaican men ages 18 to 56 years suggest that disclosure to family is affected by level of economic independence. Furthermore, negative familial responses to sexual identity significantly predicted depression. Social and structural interventions, and efforts to strengthen positive family relationships, are needed to foster an environment that enables well-being among sexual minorities in Jamaica.